Self-Efficacy in Its Influence on Students’ Anxiety in Making English Presentation - Laily, Ulul; Adi Nugroho, Him'mawan; Widyastuti, Widyastuti (PANYONARA: Journal of English Education, 2024)
Self-efficacy is individual’s belief towards their own capacity. It affects individual attitudes, emotion, and feeling. A presentation as one of learning strategy can be an instrument to discover EFL self-efficacy level. The purpose of the study is to investigate EFL students’ self-efficacy influence to their anxiety in making English presentation. This study used is quantitative research method with Ex-post-facto design by data collection technique using skala Likert of questionnaire. The results showed that the level of self-efficacy belong to EFL students is moderate to low. The significance difference of self-efficacy to students’ anxiety is also figure out by taking conclusion of students with higher self-efficacy will have lower anxiety especially in making English presentation as the achievement result.